Deposition of petroleum hydrocarbons with sediment trapped in snow in roadside areas - Mykhailova, Larysa; Fischer, Tomas; Iurchenko, Valentina (Journal of Environmental Engineering and Landscape Management, 2014)
Total petroleum hydrocarbon (TPH) deposition rates were determined along various roads using the natural snow cover as deposition trap. Daily deposition rates decreased with distance from the roads, which coincided with long-term TPH accumulation in roadside soils. Scanning electron microscopy (SEM-EDX) of the snow meltwater sediment revealed occurrence of carbon-rich plaques, which were identified as hydrocarbons using FTIR-microscopy. GC-MS revealed that the compounds extracted from the sediment consisted of an unresolved complex hydrocarbon mixture (UCM). Individual n-alkanes could not be resolved in the sediment extract, whereas TPHs extracted from soils contained a series of n-alkanes peaking at C25-C27. The proportion of UCM compounds from TPHs decreased with distance from road. We conclude that high-boiling hydrocarbons bind to coarse mineral dust and/or to splash water and vehicle spray, which preferentially deposit within a 10 m roadside strip.First published online: 19 Mar 2014